2006
DOI: 10.1080/09553000500515525
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, crystal structure and properties of bis(hexafluoroacetylacetonato)tetrazinecopper(II)

Abstract: A new complex bis(hexafluoroacetylacetonato)tetrazinecopper(II), Cu(hfac) 2 (tetz) (1), has been prepared by reaction of Cu(hfac) 2 Á xH 2 O and 1,2,4,5-tetrazine in CH 2 Cl 2 . Orange crystals suitable for X-ray diffraction analysis of 1 were obtained by slow evaporation at room temperature. Complex 1 crystallizes in the triclinic space group P 1, with a ¼ 11.4825 (7), b ¼ 13.4950(8), c ¼ 13.8328(8) Å , ¼ 104.990(1), ¼ 111.888(1), ¼ 94.245(1) , V ¼ 1886.23(19) Å 3 , R 1 ¼ 0.0507 based on 6814 independent refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…To overcome these issues, we turned our attention towards using the relatively unexplored unsubstituted 1,2,4,5‐tetrazine (tz) as a bridging ligand. It has been shown that the very low‐lying π* LUMO of the tz ring easily favours the reduction and formation of the tz .− radical anion [28–35] . The diffuse spin orbitals of tz .− ‐based radicals are ideally suited to penetrate the core‐like electron density of the lanthanide ion and reach the shielded 4 f orbitals to promote stronger coupling.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these issues, we turned our attention towards using the relatively unexplored unsubstituted 1,2,4,5‐tetrazine (tz) as a bridging ligand. It has been shown that the very low‐lying π* LUMO of the tz ring easily favours the reduction and formation of the tz .− radical anion [28–35] . The diffuse spin orbitals of tz .− ‐based radicals are ideally suited to penetrate the core‐like electron density of the lanthanide ion and reach the shielded 4 f orbitals to promote stronger coupling.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the very lowlying p*LUMO of the tz ring easily favours the reduction and formation of the tzC À radical anion. [28][29][30][31][32][33][34][35] Thed iffuse spin orbitals of tzC À -based radicals are ideally suited to penetrate the core-like electron density of the lanthanide ion and reach the shielded 4f orbitals to promote stronger coupling.M oreover, its compact size and its four easily accessible nitrogen binding sites offer ag reater possibility for the isolation of polynuclear complexes and polymeric species.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, only very few complexes with this ligand have been described. The first TTZ based complex [Cu(hfac)2(ttz)], reported in 2006 by Li et al, 31 was prepared by reaction of bis(hexafluoroacetylacetonate)copper(II) with 1,2,4,5-tetrazine in dichloromethane. In the unit cell, there are four non-equivalent Cu(II) ions, the TTZ molecules coordinating the vacant axial position of the metal ion.…”
Section: S-1245-tetrazine As Ligandmentioning
confidence: 99%